PENGARUH KOMPETENSI DAN MOTIVASI KERJA TERHADAP KINERJA GURU SMA NEGERI 13 PEKANBARU - Syaputra, Muhammad Aldi; Roesdi, Rosnelly; Pramadewi, Arwinence (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This study aims to analyze the influence of competence and work motivation on teacherperformance at SMA Negeri 13 Pekanbaru. This study uses a quantitative method with asurvey approach. The population in this study were all teachers at SMA Negeri 13 Pekanbaru,totaling 38 people. Data collection techniques were carried out through distributingquestionnaires, and the data were analyzed using multiple linear regression. Processed withthe help of SPSS version 26 program. The results of the study indicate that competence andwork motivation have a significant effect on teacher performance both partially andsimultaneously. This finding shows the importance of developing competence and strategiesfor increasing work motivation in order to support optimal teacher performance improvement.Keywords: Competence, Work Motivation, Teacher Performanc